Anonymous

# 1. Expand (x + 1)(x − 2)(x + 3)?

PreCalc

### 4 Answers

Relevance

- PuzzlingLv 72 months ago
First expand one pair of binomials (I chose x+1 and x-2):

(x² -2x + x - 2)(x + 3)

Combine like terms:

= (x² - x - 2)(x + 3)

We can now expand the multiplication. First multiply that new trinomial by x and then by 3:

x(x² - x - 2) + 3(x² - x - 2)

Distribute:

= x^3 - x² - 2x + 3x² - 3x - 6

Combine like terms:

x^3 + (-x² + 3x²) + (-2x - 3x) - 6

= x^3 + 2x² - 5x - 6

Answer:

x^3 + 2x² - 5x - 6

- az_lenderLv 72 months ago
(x+1)(x - 2) = x^2 - x - 2.

(x^2 - x - 2)(x + 3)

= x^3 - x^2 + 3x^2 - 2x - 3x - 6

= x^3 + 2x^2 - 5x - 6

- billrussell42Lv 72 months ago
(x + 1)(x − 2)(x + 3)

(x + 1)(x + 3) = x² + 4x + 3

so we have

(x − 2)(x² + 4x + 3)

x(x² + 4x + 3) – 2(x² + 4x + 3)

x³ + 4x² + 3x – 2x² – 8x – 6

x³ + 2x² – 5x – 6

Still have questions? Get answers by asking now.